The development of a new class of C-5' substituted cinchona alkaloid derivatives as efficient organocatalysts - Palacio, Carole (Trinity College (Dublin, Ireland). School of Chemistry, 2013)
Over the past three decades, the synthesis of enantiomerically pure products became a major concern in modem research. In this context, organocatalysis has emerged as a viable method and interest in this field has intensified rapidly. In particular, cinchona alkaloids - incorporating two functionalities capable of the synergestic activation of two components of a reaction in a close and chiral environment - appeared as a valuable material in new organocatalysts design. Various cinchona alkaloid derivatives have been demonstrated to be capable of the bifunctional catalysis of a number of asymmetric reactions involving the addition of an acidic pronucleophile to an electrophile incorporating hydrogen-bond accepting functionality.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.